A general review of the biomechanics of root anchorage. (30th January 2019) - Stubbs, Christopher J; Cook, Douglas D; Niklas, Karl J
Abstract : The biomechanical principles of plant anchorage systems are reviewed in the context of resisting wind-induced drag forces. The dynamic behavior of the shoot–root–soil system is shown to be extremely complex. Abstract: With few exceptions, terrestrial plants are anchored to substrates by roots that experience bending and twisting forces resulting from gravity- and wind-induced forces. Mechanical failure occurs when these forces exceed the flexural or torsional tolerance limits of stems or roots, or when roots are dislodged from their substrate. The emphasis of this review is on the general principles of anchorage, how the mechanical failure of root anchorage can be averted, and recommendations for future research.